2018
DOI: 10.12659/ajcr.907409
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Tuberculosis Mimicking Failed Back Surgery

Abstract: Patient: Female, 59Final Diagnosis: Spinal tuberculosisSymptoms: Back pain • tiredness • night sweatsMedication: —Clinical Procedure: Surgery and medical treatmentSpecialty: NeurosurgeryObjective:Challenging differential diagnosisBackground:The aim of this study was to draw attention to rare spinal infections in recurrent failed spinal surgeries.Case Report:A 59-year-old female was admitted to the hospital for back pain, which was assessed as a 9 on the visual analogue scale (VAS); the patient reported tiredne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In tubercular spondylodiscitis, there is the presence of a large adjacent soft tissue component, rim-enhancing abscesses, and bone fragments which usually compress neural elements 10 . These clinic -radiological features are not typical for tubercular spondylodiscitis, rather in various reported articles, these features are consistent with other lesions mimicking Pott's disease [11][12][13][14][15] .…”
supporting
confidence: 69%
“…In tubercular spondylodiscitis, there is the presence of a large adjacent soft tissue component, rim-enhancing abscesses, and bone fragments which usually compress neural elements 10 . These clinic -radiological features are not typical for tubercular spondylodiscitis, rather in various reported articles, these features are consistent with other lesions mimicking Pott's disease [11][12][13][14][15] .…”
supporting
confidence: 69%
“…The transverse process, as an autogenous bone, can be trimmed to the specifications of the bone defect,which not only reduces the difficulty of implantation but also ensures the strength of bone grafting and creates a large interface between the bone graft and the end plate, assuring good fusion. Compared with TMCs [23][24][25][26][27][28], TPS has superior biomechanical features and multiple transverse bone grafts can be used if the defect requires them. In our study, we used TPS combined with internal fixation; all patients showed satisfactory fusion, and the postoperative kyphosis angle was significantly corrected, indicating that TPS can effectively support the spine.…”
Section: Discussionmentioning
confidence: 99%